Amelia Opie's Lemaistre Sequence and the Romantic Occasional Poem. Issue 2 (July 2021) - Stokes, Christopher
Abstract : The occasional poem was one of the most commonly and diversely used Romantic genres, especially in informal and sociable modalities, yet is almost entirely marginalised in scholarship. This essay uses the reflexivity of Amelia Opie's sequence of birthday poems to Elizabeth Lemaistre (1815–44) to examine the dynamics of occasionality. Precisely because Opie must repeat the occasion across the sequence, the poetics of occasionality are clarified: each poem exists as a single dated action but also part of an ongoing work. This reflexive tension between the poem's character as act and text is explored through the nature of content in occasional verse; dating and temporality; and the phenomenon of the gift poem. An analysis of the Lemaistre sequence not only helps us to understand Opie's specific uses of the occasional to articulate friendship across networks of sociable affect, but also to determine more widely relevant traits of genre – not least, occasionality as a social practice and not just a literary classification.